Romantic Anatomies of Performance - Davies, J. Q. (Los Angeles, CA University of California Press, 2014)
Romantic Anatomies of Performance is concerned with the very matter of musical expression: the hands and voices of virtuosic musicians. Rubini, Chopin, Nourrit, Liszt, Donzelli, Thalberg, Velluti, Sontag, and Malibran were prominent celebrity pianists and singers who plied their trade between London and Paris, the most dynamic musical centers of nineteenth-century Europe. In their day, performers such as these provoked an avalanche of commentary and analysis, inspiring debates over the nature of mind and body, emotion and materiality, spirituality and mechanism, artistry and skill. J. Q. Davies revisits these debates, examining how key musicians and their contemporaries made sense of extraordinary musical and physical abilities. This is a history told as much from scientific and medical writings as traditionally musicological ones. Davies describes competing notions of vocal and pianistic health, contrasts techniques of training, and explores the ways in which music acts in the cultivation of bodies.
Keywords: Velluti, Giovanni Battista -- 1780-1861; Chopin, Frédéric -- 1810-1849; Malibran, Maria -- 1808-1836; Thalberg, Sigismund -- 1812-1871; Liszt, Franz -- 1811-1886; 19th Century (1801-1900); Performance; Medicine; Corporeality; Instrumentalist; Castrato; Singing; Romanticism; Cultural history; France; Germany; Italy